2000
DOI: 10.1093/bioinformatics/16.11.953
|View full text |Cite
|
Sign up to set email alerts
|

POWER_SAGE: comparing statistical tests for SAGE experiments

Abstract: michael.man@pfizer.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
122
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 14 publications
0
122
0
Order By: Relevance
“…The overall number of unique tags in both libraries was 14 968, 4092 of which appear more than once in the two libraries pooled together. (b) The number of unique tags has been plotted as a function of their occurrence in the self-renewal library (SR, white bars) or in the 24 h differentiation library (Di, gray bars) SAGE on chicken erythrocytic progenitors F Damiola et al comparison occurs by chance (Figure 2) using the Z test (Man et al, 2000). Since we have validated some of our candidate genes by real-time PCR (see below), we experimentally define the cutoff value for significantly differential genes as the largest P-value subsequently confirmed by real-time PCR.…”
Section: Differential Comparison Between Tags Abundancementioning
confidence: 99%
“…The overall number of unique tags in both libraries was 14 968, 4092 of which appear more than once in the two libraries pooled together. (b) The number of unique tags has been plotted as a function of their occurrence in the self-renewal library (SR, white bars) or in the 24 h differentiation library (Di, gray bars) SAGE on chicken erythrocytic progenitors F Damiola et al comparison occurs by chance (Figure 2) using the Z test (Man et al, 2000). Since we have validated some of our candidate genes by real-time PCR (see below), we experimentally define the cutoff value for significantly differential genes as the largest P-value subsequently confirmed by real-time PCR.…”
Section: Differential Comparison Between Tags Abundancementioning
confidence: 99%
“…This comparison showed that the chi-squared test has consistently a higher power and is more robust than the other tests, especially at low expression levels (Ͻ15 tags/50,000). Therefore, the chi-squared test, which is equivalent to the Z test, was concluded to be the preferred choice for evaluating SAGE experiments (12).…”
Section: Review: Analysis and Design Of Sage Experimentsmentioning
confidence: 99%
“…The Fisher's Exact test has been proposed by the Cancer Genome Anatomy Project for comparison of specific tags between SAGE libraries (3,12). Also, the chi-squared test has been used (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations